Characterisation of drawing parameters for fabrication of flat fibers / Katrina D. Dambul - Katrina , D. Dambul (2018)
In this thesis, drawing parameters involved in the fabrication of flat fibers were characterized. Two fundamental aspects of flat fiber fabrication were investigated, which were the effect of drawing parameters on the dimension of the flat fibers and the control of flat fiber dimensions. In the drawing of flat fibers, five parameters were identified to affect the final flat fiber dimension which were furnace temperature, preform wall thickness, draw speed, feed speed and vacuum pressure. Experimental results showed that higher furnace temperature, higher draw speed and lower feed speed resulted in capillaries with a reduced outer diameter, which led to flat fibers with reduced thickness. Preform wall thickness also influenced the thickness of the flat fibers where thin-walled preforms were more sensitive to temperature and vacuum pressure deviations due to having higher surface tension and higher viscosity. Another important finding was the furnace temperature and vacuum pressure, related to the surface tension and viscosity of the fiber being drawn, were a function of the preform material. In order to control the final flat fiber dimension, knowledge of the preform material was also essential. In single stage drawing, by varying the drawing parameters, control of capillary dimension was achieved when drawing to a diameter of 1.25 mm compared to 125 μm. Due to this, dual stage drawing technique was proposed for flat fiber fabrication. Flat fibers doped with germanium oxide were fabricated using both single and dual stage drawing, with results confirming that dual stage drawing achieved better control of the flat fiber dimension. Optical characterization performed on the doped flat fiber showed multimode propagation, a limitation due to the core dimension and to achieve single mode propagation, suitable preform core is required. It was also difficult to achieve the required flat fiber dimension using a thin-walled preform doped with germanium oxide and boron trioxide due to effects of dopant diffusion. Fabrication of multicapillary flat fibers with its lack of light guidance led to the development of the improved doped flat fibers with dual airholes. A novel and improved fabrication technique was successfully demonstrated in the fabrication of doped flat fiber with dual airholes. The doped flat fiber with dual airholes had a dimension of 165 μm x 33 μm and the airhole diameter measured was 10.8 μm. Optical characterization demonstrated that the core was able to successfully guide light and the airholes were not collapsed. This significant fabrication technique uses only a drawing tower and eliminates the need for a clean room facility. The new fabrication technique is simple, cost-effective and allows a flexible core structure arrangement using glass rods and capillaries with different refractive indices. This flexibility allows a wide range of multistructured flat fibers to be fabricated without a doped preform and the ability to fabricate core dimensions with accuracy. The multistructured flat fibers that can be fabricated using the novel fabrication technique are single core flat fiber, dual core flat fiber, multicore flat fiber, multicapillary and multicore flat fiber and multi-index flat fiber.